Effects of aging on asphalt binders modified with microencapsulated phase change material. (15th September 2019) - Kakar, Muhammad Rafiq; Refaa, Zakariaa; Worlitschek, Jörg; Stamatiou, Anastasia; Partl, Manfred N.; Bueno, Moises
Abstract: Temperature and chemical composition are governing parameters for the mechanical behavior of asphalt binders. During extreme low and high temperatures, asphalt binders can suffer thermal cracking as well as permanent deformation, respectively. The use of phase change materials (PCM) can provide asphalt binder with thermal energy storage properties for reducing the impacts of pavement temperature rise and decrease during seasonal and diurnal cycles. Studying the feasibility of using microencapsulated PCM in asphalt binders is the mean aim of this study. Accordingly, different penetration grade binders modified with microencapsulated PCM were characterized and their blends artificially aged using Rolling Thin Film Oven (RTFO) and Pressure Ageing Vessel (PAV) devices. This study also covers different size distributions of microcapsules. The thermal and rheological properties of both modified and unmodified asphalt binder under different aging conditions were analyzed using dynamic scanning calorimetry (DSC) and dynamic shear rheometer (DSR). It was found that the melting enthalpy of modified asphalt binder reduces upon aging and the reduction is dependent also on the type of binder. The results elucidate that the survival of microencapsulated PCM in asphalt binder depends on both the type of binder and the microcapsules used. Moreover, the rheological properties of modified asphalt binder determined with DSR improve due to the thermal energy released by PCM crystallization during cooling. Graphical abstract: Image 1 Highlights: The use of phase change materials (PCM) can provide asphalt binder with thermal energy storage properties for reducing the impacts of pavement temperature rise and decrease during seasonal and diurnal cycles. PCM (tetradecane) upon direct contact with bitumen is of no benefit for storing or releasing energy in asphalt binders. Microencapsulated PCM modified asphalt binders are evaluated with special focus on the survival of microcapsules during the blending and after the aging process with bitumen. The melting enthalpy of modified asphalt binder reduces upon aging and the reduction is dependent also on the type of binder. Rheological properties of modified asphalt binder determined with DSR improve due to the thermal energy released by PCM crystallization during cooling.